Serat Kasantikaning Raga Sebagai Pengayaan Naratif Lakon Figur Gathotkaca: (Tinjauan Atas Naskah Lakon Pedalangan eks koleksi J.L. Moens) - Raharja, R. Bima Slamet; Richardus, Wisma Nugraha Christianto; Haryono, Timbul (Jumantara: Jurnal Manuskrip Nusantara, 2025)
This paper discusses the manuscript collection of J.L. Moens, which contains many narratives of wayang plays. Most of the manuscripts come from the Yogyakarta puppetry tradition within the popular tradition originating from Yogyakarta and its surrounding areas. In addition to the narratives, these Javanese script texts are adorned with illustrations in the style of Yogyakarta wayang forms. Kasantikaning Raga is one of the titles of the manuscript that contains the story of Gathotkaca's journey and is divided into about 75 plays. Not many people have seen or even read this manuscript completely due to limited reach and lack of interest in exploring the rich written tradition that was revived by J.L. Moens. The text of the play, which is said to be based on the knowledge of Pakem Pancakaki, is presented as representative and 'rich' in interpretation and sanggit and is rarely presented as a pakeliran presentation. The opportunity to explore Gathotkaca's plays in Kasantikaning Raga in this study is mainly done with a framework starting from philological and literary studies. Through these two frameworks, it is possible to understand the type of language used in the text of the play, the narrative and dramatic structure of the puppetry, and the tendency of the view or ideology of the society that owns the text. The visual art aspect of the illustrations clarifies the meaning of the text and enriches the visual variants of wayang purwa in the regional expression style in Yogyakarta. The various plays about Gathotkaca are interesting to explore further because they concern the process of rites of passage for the human person in life. The Kasantikaning Raga manuscript is important as it serves as one of the lakon guidelines for recording the journey of the Gathotkaca figure, providing a systematic narrative sequence and supporting efforts to ground the lakon in pakeliran discourse and Yogyakarta traditional idioms.